A little about nuclear fusion - Amir Zacarias Mesquita (Brazilian Journal of Radiation Sciences, 2025)
On December 20, 1951, Experimental Breeder Reactor No. 1 (EBR-I), located at Argonne National Laboratory, produced enough electricity to power four light bulbs. From these modest beginnings, the civilian application of nuclear energy became a reality. The first nuclear power plant to generate energy connected to the electrical grid took place on June 27, 1954, in Obninsk (Soviet Union). There are currently around 440 nuclear reactors in operation, distributed across 50 countries. They all produce energy through the process of uranium-235 nuclear fission. However, as is well known, the conversion of mass into energy also occurs with light nuclei. When hydrogen and deuterium fuse to form a heavier nucleus, such as tritium and helium, they release energy. Stars are the largest fusion reactor power plants. A star is initially just a cloud of hydrogen. The gravitational attraction brings hydrogen atoms together, increasing pressure, density, and temperature. Kinetic energy causes collisions to the point where electrons are separated. The mass of nuclei and electrons forms plasma, which is the fourth state of matter. Hot plasma from nuclei meets the conditions for the initiation of fusion reactions. Two techniques have been developed to enable energy production in fusion reactors. The oldest (started in the mid-1950s) is magnetic confinement, in which plasmas at thermonuclear temperatures are confined by appropriate magnetic fields. The latest technique for performing fusion (begun in the late 1960s) is inertial confinement, in which tiny solid targets are compressed to very high densities using laser beams. This article briefly recalls the fundamental concepts of the energy released by nuclear fusion.